2022
DOI: 10.1111/pbi.13871
|View full text |Cite
|
Sign up to set email alerts
|

Onsite detection of plant viruses using isothermal amplification assays

Abstract: Summary Plant diseases caused by viruses limit crop production and quality, resulting in significant losses. However, options for managing viruses are limited; for example, as systemic obligate parasites, they cannot be killed by chemicals. Sensitive, robust, affordable diagnostic assays are needed to detect the presence of viruses in plant materials such as seeds, vegetative parts, insect vectors, or alternative hosts and then prevent or limit their introduction into the field by destroying infected plant mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 112 publications
(144 reference statements)
0
41
0
Order By: Relevance
“…Therefore, it can be carried out using lateral flow devices, making it suitable for onsite detection or testing in the field. The products of LAMP can be detected much faster than in standard techniques, sometimes only requiring analysis with the naked eye [ 87 ]. It has been reported that LAMP assay can be even 1000 times more sensitive than conventional PCR with equivalent specificity [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be carried out using lateral flow devices, making it suitable for onsite detection or testing in the field. The products of LAMP can be detected much faster than in standard techniques, sometimes only requiring analysis with the naked eye [ 87 ]. It has been reported that LAMP assay can be even 1000 times more sensitive than conventional PCR with equivalent specificity [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loop-mediated isothermal amplification (LAMP) is an isothermal amplification approach developed in 2000, and has become the focus of point-of-care (POC) diagnostics due to its simple operation, rapid measurement and high sensitivity of this assay (Notomi et al, 2000). As shown in Figure 2 (Bhat et al, 2022), under the strand displacement activity of the Bst DNA polymerase from Bacillus stearothermophilus in 60-65 o C, the The labeled LAMP product is diluted and applied to the lateral flow strip. After 5 to 15 min of incubation, the appearance of bands on the test and control lines indicates the presence of the target nucleic acid (Bhat et al, 2022).…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
“…As shown in Figure 2 (Bhat et al, 2022), under the strand displacement activity of the Bst DNA polymerase from Bacillus stearothermophilus in 60-65 o C, the The labeled LAMP product is diluted and applied to the lateral flow strip. After 5 to 15 min of incubation, the appearance of bands on the test and control lines indicates the presence of the target nucleic acid (Bhat et al, 2022).…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
See 2 more Smart Citations